KEBIJAKAN INTERAKTIF PADA IMPLEMENTASI KEWENANGAN DESA - Ike Wanusmawatie, Mrs. (Jurnal Ilmiah Administrasi Publik, 2012)
This research tries to analyze PP No. 72/2005 about village, especially in the side of interaction among village government and their other stakeholders. It is very important for measuring policy succession. The method used in this study is qualitative method by applying interactive model of data analysis. Result of research showed that there are ambiguity between implementing organization and the target group. It means that the goal of policy cannot be achieved because of deviation in policy formulation rather than deviation in the policy implementation. This study has important input for improvement of policy formulation, especially regarding village policy.